Relationship Between Aging, Menopause, and Eicosapentaenoic Acid/Arachidonic Acid Ratio in Women With Dyslipidemia in Tokyo - Mariko Sato; Miyuki Katai; Nanae Kondo; Masatoshi Kawana; Ken Shimamoto (Tokyo Women's Medical University Journal, 2022)
Background: The serum eicosapentaenoic acid (EPA) /arachidonic acid (AA) ratio (sEAR), which is affected by diet, is negatively correlated with the risk of coronary artery disease. The effects of aging and menopause on sEAR in women with dyslipidemia in an urban environment were investigated. Methods: To compare sEAR and serum fatty acids in 24 fractions, 89 patients were categorized into age tertiles as follows: group A, < 52 years (n = 28); group B, 52-58 years (n = 30); and group C, > 58 years (n = 31). Altogether, 82 participants with menstrual data were investigated to compare the sEAR between 66 postmenopausal patients (group M) and 16 pre-menopausal patients (group P). Results: The sEAR, serum EPA, and docosahexaenoic acid (DHA) levels were significantly higher in group C than in the other groups. The weight ratios of linoleic acid and docosatetraenoic acid were significantly lower in group C than in group A. However, sEAR was not significantly different between groups M and P. Conclusions: Among women in an urban area, the sEAR was significantly higher in the oldest group than in the other groups, with no effects on menopause. These results may be caused by the difference in the intake of EPA and DHA by age, rather than by menopause.